Sequence of Molecular Events during the Maturation of the Developing Mouse Prefrontal Cortex - Ueda, Shuhei (Mol Neuropsychiatry, 2015)
Recent progress in psychiatric research has accumulated many mouse models relevant to developmental neuropsychiatric disorders using numerous genetic and environmental manipulations. Since the prefrontal cortex (PFC) is essential for cognitive functions whose impairments are central symptoms associated with the disorders in humans, it has become crucial to clarify altered developmental processes of PFC circuits in these mice. To that end, we aimed to understand a sequence of molecular events during normal mouse PFC development. Expression profiles for representative genes covering diverse biological processes showed that while there were little changes in genes for neuroreceptors and synaptic molecules during the postnatal period, there were dramatic increases in the expression of myelin-related genes and the parvalbumin gene, peaking at postnatal day (P)21 and P35, respectively. The timing of the peaks is different from that observed in the striatum. Furthermore, the evaluation of the circuitry maturation by measuring extracellular glutamate in the PFC revealed that sensitivity to an NMDA antagonist did not become an adult-like pattern till P56, suggesting that some of the maturation processes continue till P56. The trajectory of molecular events in PFC maturation described here should help us to characterize how the processes are affected in disease model mice, an important first step for translational research.